KONSTRUKSI JURNALISTIK INVESTIGASI DALAM PERSPEKTIF ANALISIS WACANA MODEL TEUN A.VAN DIJK (SEBUAH STUDI KASUS PENEMBAKAN LASKAR FRONT PEMBELA ISLAM DI MAJALAH TEMPO) - Arvin Hardian; Tuty Mutiah; wulan Apriani; Agung Raharjo (Cakrawala - Jurnal Humaniora, 2021)
Investigation journalistic construction in the perspective of discourse analysis by Teun A. Van Dijk (A Case Study of the Islamic Defenders Front Laskar Shooting in Tempo Magazine) Van Dijk's analyst is how journalists hear and understand events. How these events are understood, through a process of meaning and mental help to understand this phenomenon as part of the news production process, which refers to the code of ethics and legal norms that apply. Meanwhile, Investigation journalism must have at least some basic elements of investigation. As; uncovering crime, wide-scale, answering all important public questions, placing the actors involved in a straightforward manner, and the public can understand the complexity of the problem. Results of the analysis; The Tempo reporter in the above case wanted to convey that the public has a position before the law. Tempo Magazine also wants to show its accuracy in compiling a cover both side chronology of the shooting of FPI members as well as protecting sources who are not willing to be identified. Furthermore, in a sematical manner, the Tempo journalist questioned Rizieq's incitement article. In the end of his report, the Tempo reporter wanted to invite his readers to describe the situation in Megamendung after Rizieq's return from Saudi Arabia by giving a strong impression of security in the hope that the public impression would be authentic.Keywords: Investigation, journalistic production.